(untitled) (Baghdad Science Journal, 2014)
A total of 60 species of aquatic oligochaetes were identified in different sites within Tigris-Euphrates basin / Iraq, including River Tigris, River Euphrates, Southern marshes ( Al-Haweiza , Al-Hammar and Al-Chebaiesh ) , Shutt Al-Germa, and Shatt Al-Arab. In River Euphrates 39 species were identified, 40 species from River Tigris and 32 species from Shatt-Al-Arab and southern marshes.The identified species were classified as four species of Family Aeolosomatidae, 54 species of Naididae ( 31 Naidinae , 8 Pristininae and 15 Tubificid worms), one species of each of Lumbriculidae ( Lumbriculus variegates ) and Lumbricidae ( Eiseiella tetraedra). Among Aeolosomatidae , Aelosoma aquaternarium, A. Liedyi, A. variegatum and A. hemprichi, in which, A. variegatum was the most frequent species, found in Euphrates river. Naidinae community were represented by five species of genus Chaetogaster, two species of each of Paranais, Slavina, & Stylaria, four species of Allonais , and seven species of each of Dero and Nais, in addition to Stephensoniana trivandrana, Specaria josinae and Ophidonais serpentina. Nais variabilis was the most abundant and frequent species in River Tigris while Stylaria lacustris & Ophidonais serpentina are abundant in River Euphrates . Species of Pristininae were representative by four species of genus Pristina and three species of genus pristinella, among them Priatina longiseta is the most abundant species.Tubificid worms, Branchuira sowerbyi and Limnodrilus hoffmeisteri were the most frequent and abundant species in the surface sediments of Iraqi waters. Beside L. hoffmeisteri , other five species of Limnodrilus, two species of Potomothrix, and a single species of Tubifex tubifex , Embolocephalus velutinus, Aulodrilus piguetia, Psammoryctides moravicus and Rhyacodrilus coccineus were recorded.